Distributed computer and communication networks : 20th International Conference, DCCN 2017, Moscow, Russia, September 25-29, 2017, Proceedings /: 20th International Conference, DCCN 2017, Moscow, Russia, September 25-29, 2017, Proceedings. (2017) - Unknown
No abstract available